A case of Pneumocystis pneumonia, with a granulomatous response and vitamin D‐mediated hypercalcemia, presenting 13 years after renal transplantation. Issue 3 (5th April 2019) - Taylor, Lindsay N.; Aesif, Scott W.; Matson, Kristine M.
Abstract: Vitamin D‐mediated hypercalcemia is an uncommon complication of Pneumocystis infection. A granulomatous response resulting from Pneumocystis infection is also atypical. In this report, we describe an exceptional case of granulomatous Pneumocystis pneumonia associated with vitamin D‐mediated hypercalcemia, in a patient who presented unusually late after renal transplantation. The patient's hypercalcemia resolved with treatment of the infection.